2009
DOI: 10.1007/s00508-008-1135-x
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of norovirus gastroenteritis in an Austrian hospital, winter 2006–2007

Abstract: The significant disruption of patient care and the cost of this single nosocomial outbreak support strict implementations of adequate and timely control measures based on evidence-based recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…Austria was one of the first EU member states to pass such a law and routinely comply with it by ensuring epidemiologic and microbiologic investigations of outbreaks of foodborne disease [18]. Several articles published in this issue of Wiener Klinische Wochenschrift [19][20][21][22][23][24] show the great potential of epidemiological outbreak investigations, in Austria as elsewhere, in recognizing sources of infections and their transmission routes. It is important that clinicians recognize this important preventive potential and actively support hospital epidemiologists, health departments and other institutions in the investigation of outbreaks and the necessary control measures.…”
Section: Investigating Outbreaks: Medical Imperative or Academic Indumentioning
confidence: 99%
“…Austria was one of the first EU member states to pass such a law and routinely comply with it by ensuring epidemiologic and microbiologic investigations of outbreaks of foodborne disease [18]. Several articles published in this issue of Wiener Klinische Wochenschrift [19][20][21][22][23][24] show the great potential of epidemiological outbreak investigations, in Austria as elsewhere, in recognizing sources of infections and their transmission routes. It is important that clinicians recognize this important preventive potential and actively support hospital epidemiologists, health departments and other institutions in the investigation of outbreaks and the necessary control measures.…”
Section: Investigating Outbreaks: Medical Imperative or Academic Indumentioning
confidence: 99%
“…25 These studies do show wide variation in the cost impact of an outbreak due in part to the wide variety in scope, size, and number of outbreaks but also due to variability in the types of cost included (e.g., interventions, attributable sick leave for staff and overtime salary, cleaning expenses, diagnosis costs), costs of various items and services, and reimbursement policies. Weaknesses of these studies include the generalizablity, as they are specific to the outbreak hospital, some focus only on extra costs and lost revenue, [23][24][25] used a case definition of symptoms only, 22 and small sample size. 24 Modeling studies, which may overcome some of these limitations, estimate a case of norovirus to the hospital is an average $6237 26 and provide cost estimates for outbreaks of various sizes in differing size hospital wards.…”
Section: Wwwlandesbiosciencecom Human Vaccines and Immunotherapeuticsmentioning
confidence: 99%
“…21 Several studies specifically evaluated the cost of various norovirus hospital outbreaks (range: $37 968 to ≤201 690 per outbreak) in developed countries. [22][23][24][25] One study found that over a two year period outbreaks in the United Kingdom cost up to ≤1.2 million. 25 These studies do show wide variation in the cost impact of an outbreak due in part to the wide variety in scope, size, and number of outbreaks but also due to variability in the types of cost included (e.g., interventions, attributable sick leave for staff and overtime salary, cleaning expenses, diagnosis costs), costs of various items and services, and reimbursement policies.…”
Section: Wwwlandesbiosciencecom Human Vaccines and Immunotherapeuticsmentioning
confidence: 99%
“…Alleine für die internistische Abteilung ergeben sich dabei zusätzlich Kosten von mehr als € 80 000. Der NA endet durch Verbesserung der Händehygiene und Flächendesinfektion[29]. Die in dieser Arbeit verwendete Methode der systematischen Übersichtsarbeit hat Vor-aber auch Nachteile.…”
unclassified